Kardinah in the Frame of Women's Struggle in Tegal 1911 – 1927 - Cahyani Indrawati; Nanda Julian Utama (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2023)
This article reviews Kardinah's track record in Tegal. The main issues raised were Kardinah's thoughts and role in fighting for women and some impacts of the struggle she carried out in Tegal in 1911 - 1927. The purpose of this research was to reveal Kardinah's role in these aspects of the problem. The scope of this research is in the area of Tegal, Central Java with a research time limit of 1911-1927. The research method used is the historical research method which consists of several stages starting from heuristics, source criticism, interpretation, and historiography. The main sources for this research include government archives, contemporary newspapers, and similar research results. From this research, we found several results in the form of ideas and steps taken by Kardinah to bring Javanese women toward a better life. The initial step was carried out through the provision of educational facilities in the form of sekolah kepandaian putri, Wisma Pranawa. Kardinah also played an important role in promoting local silver crafts and developing Tegalan batik motifs. In the health sector, Kardinah seeks to provide medical facilities which is realized through the establishment of the Kardinah Hospital. Kardinah's progress in women's struggles, which is rarely known to the public outside of her position as Kartini's shadow, makes this study necessary to carry out.